If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -5 = 19 + -1p Reorder the terms: -5 + 2p = 19 + -1p Solving -5 + 2p = 19 + -1p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add 'p' to each side of the equation. -5 + 2p + p = 19 + -1p + p Combine like terms: 2p + p = 3p -5 + 3p = 19 + -1p + p Combine like terms: -1p + p = 0 -5 + 3p = 19 + 0 -5 + 3p = 19 Add '5' to each side of the equation. -5 + 5 + 3p = 19 + 5 Combine like terms: -5 + 5 = 0 0 + 3p = 19 + 5 3p = 19 + 5 Combine like terms: 19 + 5 = 24 3p = 24 Divide each side by '3'. p = 8 Simplifying p = 8
| 5x+(3x+12)=180 | | 4X-8=3X-5 | | 3x-30=x+10 | | 9.8-5p=4p-1 | | x+.5x=10 | | 4x-6=2+12x | | K^2+16=0 | | 10x-1=8x+21 | | -2(3-x)=4x+10 | | -4(-1+7b)+2b=-100 | | 4x+3=2+6x | | A=3a-2b-4c | | K^2+6k+9=0 | | 10y-8=4-6y | | 3(2x-1)+4(3x-2)= | | (-5*-5+8-3)/3+6= | | (-5x-5+8-3)/3+6= | | 2w^2-3w=0 | | 2x+10=62-7x | | 3x-14+4x-22=90 | | 5(2d+8)=2(3d+24) | | f=ma+b | | 9a^2-(3a-2b)(3a-2b)=0 | | 15x+19=5x+239 | | 3x+2=-1x+3 | | x^3+8x-4x^2=0 | | x^3+8x^2-4x=0 | | 8s-4(2s+3)= | | 4(r-1)+5r+3= | | x^3-6x^2-4x=0 | | 2(x-10)=-3(4x+2) | | 2(x-10)=-3(4x-2) |